Evaluating Silicon Carbide-Based Slurries and Molds for the Manufacture of Aircraft Turbine Components by the Investment Casting - Paweł Wiśniewski (Crystals, 2020)
Silicon carbide (SiC) is a promising material for the fabrication of ceramic shell molds due to its high mechanical strength, hardness, thermal shock resistance, and thermal conductivity compared with commonly used slurries. This article describes the test results of casting materials, i.e., SiC-based powders and aqueous binders with aluminum oxide nanoparticles, as well as the parameters of slurries used for prime coats and structural layers. Tests were also performed to evaluate the physical and mechanical properties of SiC-based shell molds for the manufacture of aircraft turbine components. Two SiC-based slurries with solid concentrations of 65 and 70 wt.% were prepared, and their viscosity, density, pH, quantity, thickness, and copper plate adhesion (plate weight test) were investigated. Fourteen days were required to prepare and evaluate the slurry parameters. The results showed that SiC-based slurries had a Zahn cup #4 outflow time of 33.1 s to fabricate the first two coats and 14.8 s to fabricate the shell mold structural layers. Three series of SiC-based shell mold samples were prepared: after dewaxing (PW1), after burnout preheating at 700 °C (PW2), and after annealing at 1200 °C (PW3). The bending mechanical strength, Young’s modulus, and Weibull’s modulus of the samples were calculated, and the roughness (Ra and Rq) and microstructures of samples were also analyzed (SEM). Inner defects were evaluated by CMT (µCT). The Ra and Rq values of the prime coat of the SiC-based shell mold did not exceed 5 µm. The fabricated SiC shell molds had bending mechanical strengths from 1.21–2.28 MPa, Young’s modulus of 102.97–207.66 MPa, and a Weibull’s modulus from 5.36–9.94. The shell molds fabricated on the technical scale met the requirements specified for industrial shell molds.